Efektivitas Mindfulness-Based Cognitive Therapy (MBCT) untuk Mengurangi Gangguan Kecemasan dan Depresi pada Orang Dewasa - Mery Mirna Leni; Meidiana Dwidiyanti; Alifiati Fitrikasari (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the effectiveness of Mindfulness-Based Cognitive Therapy (MBCT) in reducing anxiety and depression disorders in adults. The method used is a systematic review. The results of this study indicate that the MBCT intervention can reduce symptoms of anxiety and depression in adult patients. Effective MBCT intervention is carried out once a week for eight sessions, and each session is carried out for 2 hours under the guidance of a therapist. MBCT interventions consist of providing patients health education about anxiety symptoms, mindfulness training and meditation exercises by therapists, and independent activities at home for 15-30 minutes according to guidelines. This study concludes that Mindfulness-Based Cognitive Therapy (MBCT) has been proven effective in reducing anxiety and depression disorders in adults. Therefore, giving non-pharmacological therapy such as MBCT also has benefits besides pharmacological treatment. Keywords: Depression, Anxiety Disorders, Adult Patients, Mindfulness-Based Cognitive Therapy.